THE RECOVERY OF CONSTITUTIONAL LOSSES BY THE CONSTITUTIONAL COURT - Pratama, Novan Mahendra (Faculty of Law Universitas Trunojoyo Madura, 2020)
The Constitutional Court's decision does not necessarily lead to the restoration of constitutional rights. This will be interesting to be examined because the state, in this case represented by the Constitutional Court, can only recover the constitutional losses suffered by citizens if it issues a decision. However, there are also citizens who still feel that their losses have not been recovered by the issuance of this decision. Then how can the Constitutional Court recover such constitutional losses by still referring to the constitution and laws and regulations? This research method uses normative research methods. The results of this study indicate that the Constitutional Court decisions do not always lead to the restoration of the constitutional rights of the injured citizens. Then what are the other ways to recover the constitutional losses still experienced by citizens. This constitutional loss really needs to be restored because its existence is guaranteed in the constitution and all branches of state power are obliged to respect it by not committing violations even to the point of loss